2015
DOI: 10.1111/jen.12215
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and numerical relationships of arthropod communities associated with key pests of maize

Abstract: Pest management largely focuses on managing individual pest species with little concern for the diverse communities that co-occur with key pests and potentially shape their population dynamics. During anthesis, we described the foliar arthropod communities on 53 maize farms throughout the region of eastern South Dakota. The resulting communities were examined for trends in local associations in the abundances of taxa with key pests in the system (rootworms [Diabrotica spp.], European corn borers [Ostrinia nubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 70 publications
(108 reference statements)
4
12
0
Order By: Relevance
“…As discussed previously, the lack of available prey or hosts during the first 4 weeks of corn growth probably delayed colonization and subsequent population buildup of many predators and parasitoids. When correlating arthropod abundance with predominant herbivores on corn plants at anthesis, aphid populations corresponded with numerical responses to multiple predators including coccinellids, anthocorids, spiders, syrphids, and carabids . Likewise, thrips, aphids and cicadellids were the most prevalent herbivores in our study, and the foliar and aerial sampling data showed reductions in thrips that coincided with reductions in anthocorids.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…As discussed previously, the lack of available prey or hosts during the first 4 weeks of corn growth probably delayed colonization and subsequent population buildup of many predators and parasitoids. When correlating arthropod abundance with predominant herbivores on corn plants at anthesis, aphid populations corresponded with numerical responses to multiple predators including coccinellids, anthocorids, spiders, syrphids, and carabids . Likewise, thrips, aphids and cicadellids were the most prevalent herbivores in our study, and the foliar and aerial sampling data showed reductions in thrips that coincided with reductions in anthocorids.…”
Section: Discussionsupporting
confidence: 58%
“…When correlating arthropod abundance with predominant herbivores on corn plants at anthesis, aphid populations corresponded with numerical responses to multiple predators including coccinellids, anthocorids, spiders, syrphids, and carabids. 54 Likewise, thrips, aphids and cicadellids were the most prevalent herbivores in our study, and the foliar and aerial sampling data showed reductions in thrips that coincided with reductions in anthocorids. In some cases, exposure to neonicotinoids can also influence natural enemies' ability to find hosts.…”
Section: Routes Of Exposuresupporting
confidence: 66%
See 2 more Smart Citations
“…Moreover, data should be gathered in a targeted manner focusing on testable risk hypotheses formulated during the problem formulation phase of ERA (Raybould 2006). To optimize the usefulness of field trials, EFSA recommends to target those taxa which are considered the most informative to ERA and which are expected to be sufficiently abundant to support sound statistical analyses (Duan et al 2006;Rauschen et al 2010;Comas et al 2013Comas et al , 2015Romeis et al 2014;Lundgren et al 2015), and to perform field trials with sufficient plot size and replication (Candolfi et al 2000;Perry et al 2009;Semenov et al 2013;van der Voet and Goedhart 2015).…”
Section: Extended Hazard Identificationmentioning
confidence: 99%